Prevention of Crack In Stretch Flanging Process Using Hot Stamping Technique - Y., Mohd Syafiq; Zamzuri, Hamedon; Wan Azila, Aziz; A. R., Yusoff (IOP Publishing, 2017)
Demand for enhancing of passenger safety as well as weight reduction of automobiles has increased the use of high strength steel sheets. As a sheet metal is a lightweight having high strength is suitable for producing automotive parts such as white body panel. The stretch flanging of the high strength steel sheet is a problem due to high springback and easy to crack. This study uses three methods to stretch flange the sheets; using lubricants, shear-edge polishing and hot stamping. The effectiveness of these methods will be measured by comparing the flange length of each methods can achieved. For stretch flange with lubricant and polished sheared edge, the flange length failed to achieve the target 15 mm while hot stamping improved the formability of the sheet and preventing the occurrence of the springback and crack. Hot stamping not only improved formability of the sheet but also transformed the microstructure into martensite thus improve the hardness and the strength of the sheet after been quenched with the dies.